Mary Jugg Molek and her first writings - Irena Milanič (Acta Neophilologica, 1999)
In this paper I present the life and work of Mary Jugg Molek (1909-1982) an American writer of Slovene roots . So far she was mainly known as the wife and translator of her much more famous husband Ivan Molek, a prolific writer and a very influential Slovene-American editor. Whilst Mary Molek's publications of the seventies have already been reviewed, most of her earlier writings, in particular those of the thirties and forties have been overlooked.